Els verbs de tipus «naixtre» al Baix Vinalopó - Segura i Llopes, Carles (Caplletra. Revista Internacional de Filologia, 1999)
The aim of this paper is to analyze a sample of verb morphology belonging to the speech of the Valencian area of Baix Vinalopó, in order to ascertain the effect of Catalan standard forms upon traditional spoken tendencies, once Catalan has been present at school or in the mass media for more than twelve years. More specifically, there is an ongoing morphological change, affecting a number of infinitives, future and conditional tenses of the «naixtre», «ixtrà» or «convenstre» type, as different from the general forms in Catalan «nàixer», «eixirà» and «convèncer».